2017
DOI: 10.1037/dev0000267
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of maternal sensitivity and toddler engagement of mother in predicting self-regulation.

Abstract: Using data from the Early Head Start Research and Evaluation Project, a cross-lag mediation model was tested to examine longitudinal relations among low-income mothers' sensitivity; toddlers' engagement of their mothers; and toddler's self-regulation at ages 1, 2, and 3 years (N = 2,958). Age 1 maternal sensitivity predicted self-regulation at ages 2 and 3 years, and age 2 engagement of mother mediated the relation between age 1 maternal sensitivity and age 3 self-regulation. Lagged relations from toddler self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 67 publications
2
16
0
7
Order By: Relevance
“…The lack of a first order correlation between maternal sensitivity and inhibition could be in line with a suggestion that responsive parenting may operate through increased child engagement rather than through inhibition (Ispa, Su‐Russell, Palermo & Carlo, ). Specifically, that regulated and engaged children are more prone to both seek out and be receptive to learning opportunities, rather than prohibiting impulses per se.…”
Section: Discussionsupporting
confidence: 80%
“…The lack of a first order correlation between maternal sensitivity and inhibition could be in line with a suggestion that responsive parenting may operate through increased child engagement rather than through inhibition (Ispa, Su‐Russell, Palermo & Carlo, ). Specifically, that regulated and engaged children are more prone to both seek out and be receptive to learning opportunities, rather than prohibiting impulses per se.…”
Section: Discussionsupporting
confidence: 80%
“…Second, in cross‐lagged longitudinal research, there are potential issues arising from using the same measures at different ages. In the research on eating and weight in childhood, this can be helped by measuring general constructs (such as intrusive parenting, negative control, or pressure to eat) and using two or more measuring occasions that are separated by no more than about 3 years . At times, adjustments to measures are needed across ages, or additional measures included .…”
Section: Resultsmentioning
confidence: 99%
“…In the research on eating and weight in childhood, this can be helped by measuring general constructs (such as intrusive parenting, negative control, or pressure to eat) and using two or more measuring occasions that are separated by no more than about 3 years. 106,152,231,266,274,289,310,342,343 At times, adjustments to measures are needed across ages, 106,264 or additional measures included. 286 In developmental research, crosslagged designs have been used over longer periods.…”
Section: Limitationsmentioning
confidence: 99%
“…The examiners were trained to a minimum of 85% agreement with a master trainer. This measure of self‐regulation has been shown to be reliable (Raikes, Robinson, Bradley, Raikes, & Ayoub, 2007) and is used commonly in previous EHSREP studies (e.g., Ispa et al, 2017; Streit et al, 2017) based on the conceptualization that self‐regulatory abilities include aspects of negative emotionality, attentional control, persistence, and flexibility (Raikes et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Support for the mutual regulation model stems from studies suggesting that responsive parenting behaviors support children’s self‐regulation and academic abilities whereas less sensitive or harsher parenting behaviors diminish those abilities (Blair & Raver, 2012; Ispa, Su‐Russell, Palermo, & Carlo, 2017). For example, Kopystynska, Spinrad, Seay, and Eisenberg (2016) found that when mothers used sensitive, polite suggestions and affectionate encouragement to redirect toddlers’ behaviors, the children were likely to exhibit enhanced self‐regulation abilities a year later which, in turn, facilitated their academic functioning 3 years later.…”
Section: Introductionmentioning
confidence: 99%